Strategi Pencegahan Money Politic Melalui Pengawasan Pertisipatif Masyarakat Di Kecamatan Kalianget - Sama Sama (Jurnal Hukum dan Sosial Politik, 2023)
The democratic party in the State of Indonesia is realized through the General Election mechanism, which is carried out at various levels from the village to the district. Democracy is often interpreted as the people, by the people, and for the people, or more clearly, the term democracy is the overall highest power in the hands of the people. This type of research is a descriptive research and qualitative research approach. This research was conducted in Kalianget District, Sumenep Regency. There are three strategies for preventing crime violations, the first is Primary Crime Prevention, the second is Secondary Crime Prevention, and the third is Tertiary Crime Prevention. Of the three concepts, the Primary Prevention Strategy is more effective in conducting political socialization. This strategy aims to increase public awareness and knowledge through political socialization so that money politics in society does not occur during the General Election process in Kalianget District.